Xylitol Production from Oil Palm Empty Fruit Bunches (OPEFB) Via Simultaneous Enzymatic Hydrolysis and Fermentation Process - Efri Mardawati; Nadya Maharani; Dwi Wahyudha Wira; Budi Mandra Harahap; Tri Yuliana; Een Sukarminah (Journal of Industrial and Information Technology in Agriculture, 2018)
Oil palm empty fruit bunches (OPEFB) are the waste of palm oil processing and lignocellulosic biomass that can be used as raw material for xylitol production. In this research, bioconversion of xylitol using the Simultaneous Saccharification and Fermentation (SSF) process in one reactor with a short time and could save the cost. Pretreatment requires to degrade the lignin compound with thermal pretreatment. Hydrolysis of OPEFB performs enzymatically by commercial xylanase enzyme that is Cellic Htec2 and continued with fermentation by yeast Debaryomyces hansenii. The research used experimental and descriptive analysis that covers of variation of OPEFB substrate concentration (7.5%, 10%, 15%, 20%) on specific growth rate (µ), the yield of xylitol and substrate utilization. The results showed that an increase of OPEFB substrate concentration affected by the increase of specific growth rates  (μ) are 0.091/h, 0.094/h, 0.095/h and 0.126/h. It also affected to the decreasing of xylitol yield on 42 hours fermentation are 0.201 g/g; 0.189 g/g; 0.170 g/g; and 0.104 g/g.